The U2 snDNA Is a Useful Marker for B Chromosome Detection and Frequency Estimation in the Grasshopper Abracris flavolineata - Milani, Diogo [UNESP]; Palacios-Gimenez, Octavio M. [UNESP]; Cabral-de-Mello, Diogo C. [UNESP] (Karger, 2017)
In this study, we describe a strategy to determine the presence of B chromosomes in the living grasshopper Abracris flavolineata by FISH using U2 snDNA as a probe in interphase hemolymph nuclei. In individuals without B chromosomes, (0B) 2 dot signals were noticed, corresponding to A complement U2 snDNA clusters. In +1B and +2B individuals, 4 or 8 additional signals were noticed, respectively. In all cases, the absence or presence of 1 or 2 B chromosomes correlated in hemolymph and in somatic or germline tissues, validating the efficiency of the marker. Our data suggest that the B chromosome of A. flavolineata is present in all somatic tissues. B-carrying individuals showed the same number of B chromosomes in germ and somatic cells, suggesting that the B is mitotically stable. The marker was used to compare B chromosome frequency in the analyzed population with a sample collected previously, in order to test for B frequency changes and differences of B chromosome prevalence among sexes, but no statistically significant differences were noticed. The identification of living animals harboring B chromosomes will be very useful in future studies of B chromosome transmission, as well as in functional studies involving RNA analysis, thus contributing to the understanding of evolutionary history and the possible role of the B chromosome in A. flavolineata. (C) 2017 S. Karger AG, Basel
Keywords: B chromosome; Cytogenetics; FISH; Interphase nuclei; U2 snDNA